FAKTOR RISIKO KEMATIAN NEONATUS DENGAN PENYAKIT MEMBRAN HIALIN - , Alifah Anggraini, dr. Sumadiono, Sp.A(K) ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Background: The infant mortality rate (IMR) in Indonesia Demographic and Health Survey (IDHS) 2002-2003 was 35 per 1000 live births. Twothirds of infant deaths are neonatal deaths and mainly caused by premature labor. Hyaline membrane disease (HMD) is the most common cause of morbidity and mortality in preterm infants. Research on the factors that play a role in neonatal mortality could support Millenium Development Goals implementation by developing appropriate prevention and management. Objective: To determine risk factors affecting mortality of hyaline membrane disease patients at Maternal and Perinatology Unit Dr. Sardjito Hospital Yogyakarta. Methods: A case-control study was done based on secondary data from a data base and medical records of patients who were hospitalized and diagnosed with HMD at Maternal and Perinatology Unit Dr.Sardjito Hospital Yogyakarta during 2007 to 2011. Result: The proportion of deaths in neonates with hyaline membrane disease at Dr. Sardjito Hospital during 2007 - October 2011 is 52%. Asphyxia is a risk factor for mortality in neonates with hyaline membrane disease (OR 4.97, 95% CI 2.39 - 10.28). Analysis with logistic regression method shows that asphyxia is an independent risk factor for neonatal mortality in neonates with hyaline membrane disease (aOR 5.15, 95% CI 2.43 - 10.91). Conclusion: Asphyxia is an independent risk factor for neonatal mortality in neonates with hyaline membrane disease. An appropriate resuscitation in asphyxia management is necessary to reduce risk of mortality in neonates with hyaline membrane disease.